Genomic re-assessment of the transposable element landscape of the potato genome - Zavallo, Diego (2020)
Transposable elements (TEs) are DNA sequences with the ability to autoreplicate and move throughout the host genome. TEs are major drivers in stress response and genome evolution. Given their significance, the development of clear and efficient TE annotation pipelines has become essential for many species. The latest de novo TE discovery tools, along with available TEs from Repbase and sRNA-seq data, allowed us to perform a reliable potato TEs detection, classification and annotation through an open-source and freely available pipeline (https://github.com/DiegoZavallo/TE_Discovery). Using a variety of tools, approaches and rules, we were able to provide a clearly annotated of characterized TEs landscape. Additionally, we described the distribution of the different types of TEs across the genome, where LTRs and MITEs present a clear clustering pattern in pericentromeric and subtelomeric/telomeric regions respectively. Finally, we analyzed the insertion age and distribution of LTR retrotransposon families which display a distinct pattern between the two major superfamilies. While older Gypsy elements concentrated around heterochromatic regions, younger Copia elements located predominantly on euchromatic regions. Overall, we delivered not only a reliable, ready-to-use potato TE annotation files, but also all the necessary steps to perform de novo detection for other species.